Pengaruh Economic Value Added dan Rasio Profitabilitas terhadap Return Saham Perusahaan Manufaktur di Bursa Efek Indonesia - Ferawati Zhang (Universitas Negeri Medan (UNIMED), 2017)
Over recent years a new approach to assessing company performance has been developed, known as Economic Value Added (EVA). EVA attemps to measure to value added produced by a firm by taking into cost of capital, where traditional measuring instrument has never been included. In the other hands, investors often use traditional financial ratios like ROA, ROE and EPS to measure share return. The problem identification is how EVA and financial ratios ROA, ROE and EPS influence to share return. The purpose target of this research is to evaluate and analysis the influences of Economic Value Added and profitability ratios Return on Asset, Return on Equity and Earning per Share to Return of manufacturing business shares in Indonesia Stock Exchange, either through partial and also by simultaneous. Research samples are entire manufacturing business which enlist in Indonesia Stock Exchange since year 2005-2008 active to and also publish financial statement during perception year and consistence obtain profit and share dividend during perception year, that is counted 20 companies. Data collecting conducted by taking financial statement documentation of Indonesia Stock Exchange and processed to use statistical test of doubled linear regression by means of SPSS 16.0. Result of this research prove that EVA and financial ratios ROA, ROE and EPS by simultaneous influence share return, but by partial only ROE having an effect on by significant to share return, while EVA, ROA and EPS do not have an effect on by significant to share return. Coefficient of R Square is 0,211. It indicates that EVA, ROA, ROE and EPS can explain 21,1% to dependent variable and 78,9% explained by other independent variable which do not analysis